If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(-8 + -6b) = 6 (-8 * -3 + -6b * -3) = 6 (24 + 18b) = 6 Solving 24 + 18b = 6 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 18b = 6 + -24 Combine like terms: 24 + -24 = 0 0 + 18b = 6 + -24 18b = 6 + -24 Combine like terms: 6 + -24 = -18 18b = -18 Divide each side by '18'. b = -1 Simplifying b = -1
| 61=-5(1-8v)-7v | | -6=-6(-7-8n) | | -60=3(-7x+8) | | 7(3r+6)=21 | | 60=6(6m-7)-6 | | -4(3n-4)=-56 | | -25=-1-6(1+3x) | | k^3=144k | | -7(1+3p)=-70 | | 10x^2+40x+2=0 | | 8x^3+64=0 | | 3(2n+4)+5(3-2n)=7-2n | | -2=-7(4a+7) | | 3(2+5x)=-39 | | 6(8k+8)=0 | | 3-4x=0 | | y-4(3)=0 | | -3x+6=2 | | 64y^2+112y+49=0 | | -6=29x | | 4+7z=3z-20 | | y-3(3)=0 | | 4+7z=20-3z | | 2l+2w=264 | | 4v-5=17 | | 2l+2w=264(10w) | | (4x+8)(3x-2)=0 | | 2(0)+y=42 | | 1=y+3(y-9) | | 2.4=2.7 | | 25p^2-49p-2=0 | | 6(x+3)=3(2x+9)-9 |